1996
DOI: 10.1897/1551-5028(1996)015<1577:tiopam>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

THE INFLUENCE OF pH AND MEDIA COMPOSITION ON THE UPTAKE OF INORGANIC SELENIUM BY CHLAMYDOMONAS REINHARDTII

Abstract: Abstract-The uptake of inorganic selenium species, selenate and selenite, by the green alga Chlamydomonas reinhardtii Dang was examined as a function of pH over the range 5 to 9 and in media with varying concentrations of major ions and nutrients using 75 Se as a radiotracer. Little difference was noted in the uptake of selenate as a function of pH, with the maximum uptake occurring at pH 8; however, selenite uptake increased substantially at the lower pH values. Selenate uptake was significantly decreased by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 24 publications
6
33
0
Order By: Relevance
“…Uptake of Se was significantly reduced by P additions in most cases but not by N additions. These observations are consistent with the results of previous studies using pure unicellular cultures [14,22]. For example, Wang and Dei [14] demonstrated that Se(IV) accumulation in both diatoms ( T. pseudonana and Skeletonema costatum ) and a green alga ( Chlorella autotrophica ) was inversely dependent on the ambient P and Si concentrations.…”
Section: Discussionsupporting
confidence: 92%
“…Uptake of Se was significantly reduced by P additions in most cases but not by N additions. These observations are consistent with the results of previous studies using pure unicellular cultures [14,22]. For example, Wang and Dei [14] demonstrated that Se(IV) accumulation in both diatoms ( T. pseudonana and Skeletonema costatum ) and a green alga ( Chlorella autotrophica ) was inversely dependent on the ambient P and Si concentrations.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, variation of metal K u values among different batches of experiments is rather small. Anionic metals [e.g., Cr(VI) and Se(IV)] are generally taken up at a slower rate, probably because of competition with major anions in seawater [28][29][30]. As found in previous studies, the uptake rate was highest for metals (e.g., Cd and Zn) that require facilitated transport in which SH-containing ligands are involved in metal binding [24].…”
Section: Metal Uptake Rate Constants In Bivalvesmentioning
confidence: 87%
“…Because selenite may be taken up mainly through anionic transporters, it appears that the membrane permeability brought by a change in Ca 2+ concentration may be responsible for a change in Se influx. Using only one Ca 2+ concentration treatment (+1 mM Ca 2+ ), Riedel and Sanders [34] showed no significant effect of Ca 2+ on selenite uptake by the green alga Chlamydomonas reinhardtii . The influence of Ca 2+ on Zn influx may be a result of accidental uptake of Zn through the Ca channel.…”
Section: Discussionmentioning
confidence: 99%